PERAN STAKEHOLDER PARIWISATA DALAM PENGEMBANGAN PULAU SAMALONA SEBAGAI DESTINASI WISATA BAHARI - Reski Amalyah; Djamhur Hamid; Luchman Hakim (Jurnal Administrasi Bisnis, 2016)
Samalona Island located in the Makassar Strait, which is one of the several islands in the cluster of Spermonde islands in the Makassar city. Development in Samalona Island involves the tourism stakeholders consisting of government, private sector, and the community. The purpose of this study were to identify the profile and tourism attractions on the Samalona Island, the role of stakeholders in the Samalona Island development, and the supporting and inhibiting factors of stakeholder roles in Samalona Island development. Samalona Island is an island that has the potential of maritime tourism, such as snorkeling. The development of the Samalona Island involves the tourism stakeholders consisting of government through the Disparekraf Makassar, tourism businesses and local communities. The stakeholders roles in the development of Samalona Island include the provision of infrastructure, human resource development, local development, promotion, and CSR (Corporate Social Responsibility). Supporting factors in Samalona Island development is involvement of local communities in the management and support of the private sector. Inhibiting factors in the development of the Samalona Island are Disparekraf roles is not maximized, local communities as a professional tour players are still lacking, and lack of coordination of the various stakeholders. Keywords: Stakeholders, Samalona Island, Marine Tourism Development ABSTRAK Pulau Samalona terletak di Selat Makassar yang merupakan salah satu dari beberapa pulau di dalam gugusan Kepulauan Spermonde yang ada di Kota Makassar. Pengembangan Pulau Samalona melibatkan stakeholder pariwisata yang terdiri dari pemerintah, swasta, dan masyarakat. Penelitian ini bertujuan untuk mengetahui profil daya tarik dan atraksi wisata di Pulau Samalona, peran stakeholder dalam pengembangan Pulau Samalona, dan faktor pendukung dan penghambat peran stakeholder dalam pengembangan Pulau Samalona. Hasil penelitian ini menunjukkan bahwa Pulau Samalona merupakan pulau yang memiliki potensi bahari sehingga kegiatan utama yang dilakukan wisatawan yaitu snorkeling. Pengembangan Pulau Samalona melibatkan stakeholder pariwisata yang terdiri dari pemerintah melalui Disparekraf Kota Makassar, pelaku usaha pariwisata, dan masyarakat lokal Pulau Samalona.  Peran stakeholder dalam pengembangan Pulau Samalona berupa penyediaan sarana prasarana, pembinaan sumber daya manusia, pemberdayaan masyarakat lokal, promosi, dan CSR (Corporate Social Responsibility). Faktor pendukung pengembangan Pulau Samalona adalah keterlibatan masyarakat lokal Pulau Samalona dalam pengelolaan dan dukungan pihak swasta. Faktor penghambat pengembangan Pulau Samalona yaitu peran Disparekraf belum maksimal, masyarakat lokal sebagai pelaku wisata belum profesional, dan kurangnya koordinasi dari berbagai stakeholder. Kata Kunci: Stakeholder Pariwisata, Pulau Samalona, Pengembangan Wisata Bahari